Pengaruh Foreign Direct Investment, UMKM, Infrastruktur dan Koperasi Terhadap Pertumbuhan Ekonomi serta Dampaknta pada Penurunan Pengangguran di Provinsi DKI Jakarta - Johan, Ria Susanti; Supandi, Agus (JUDICIOUS, 2025)
Economic growth is influenced by several important factors, including investment, infrastructure development, development of small and medium enterprises, and developments in the level of income distribution. DKI Jakarta Province is one of the provinces that has very potential resource potential. DKI Jakarta Province is also the gateway to the island of Java which allows DKI Jakarta's economic growth rate which should be better than other provinces in Java. The purpose of this study is to examine and analyze the influence of foreign direct investment, MSMEs, infrastructure and cooperatives on economic growth and their impact on reducing unemployment. The research method used in this research is Ordinary Least Square, Multiple Linear Regression and simple panel data. The research variables used were FDI, MSMEs, Infrastructure and cooperatives, which in the next study functioned as independent variables affecting economic growth which functioned as the dependent variable, and unemployment functioned as the dependent variable. The results showed that both simultaneously and partially FDI, MSMEs, Infrastructure and Cooperatives had a positive and significant effect on economic growth. Economic growth has a positive and significant effect on unemployment. The research findings show that the amount of foreign investment, MSMEs, infrastructure and cooperatives on economic growth in the Special Capital Region of Jakarta is 67.7 percent. The next finding is that the infrastructure variable is the dominant variable that affects economic growth in DKI Jakarta.